Taming Tumor Glycolysis and Potential Implications for Immunotherapy - Ganapathy-Kanniappan, Shanmugasundaram (Frontiers in Oncology, 2017)
Immune evasion and deregulation of energy metabolism play a pivotal role in cancer progression. Besides the coincidence in their historical documentation, and concurrent recognition as hallmarks of cancer both immune evasion and metabolic deregulation are functionally linked as well. For example, the metabolic phenotype, particularly tumor glycolysis (aerobic glycolysis) impacts the tumor microenvironment (TME) which in turn acts as a major barrier for successful targeting of cancer by antitumor immune cells and other therapeutics. Similarly, in the light of recent research it has been known that some of the immune sensitive antigens which are down-regulated in cancer may also be induced by cellular/ metabolic stress. For instance, cancer cells down-regulate the cell surface ligands such as MHC class I chain-related (MIC) protein-(A/ B) that are normally up-regulated in disease/pathological conditions. Noteworthy, the MIC-A/B are recognized by natural killer (NK) cells for immune elimination. Interestingly, MIC-A/B are stress-inducible as demonstrated by oxidative stress, and other cellular-stress factors. Consequently, stimulation of metabolic stress has also been shown to sensitize cancer cells to NK cell mediated cytotoxicity. Taken together, data from recent reports imply that dysregulation of tumor glycolysis could facilitate induction of immune sensitive surface ligands leading to increased efficacy of antitumor immunotherapeutics. Nonetheless, dysregulated tumor glycolysis may also impact the TME and alter it from acidic, low-pH into therapeutically-desirable TME that can enhance the penetrability of antitumor immune cells. In this mini-review, targeting tumor glycolysis has been discussed to evaluate its potential implications to enhance and/or facilitate anticancer immunity.